LT-LiMn0.5Ni0.5O2: a unique co-free cathode for high energy Li-ion cells. Issue 84 (24th September 2021) - Shi, Boyu; Gim, Jihyeon; Li, Linze; Wang, Chongmin; Vu, Anh; Croy, Jason R.; Thackeray, Michael M.; Lee, Eungje
Abstract : A new 'low-temperature (LT)' polymorph of LT-LiMn0.5 Ni0.5 O2, which has a lithiated-spinel-like structure, shows high capacity with stable cycle stability. Abstract : A novel LiMn0.5 Ni0.5 O2 cathode with a predominant, partially-disordered lithiated-spinel structure has been prepared by a 'low temperature' (LT) synthesis. Li/LT-LiMn0.5 Ni0.5 O2 cells operate between 5.0 and 2.5 V with good cycling stability, yielding a capacity of 225 mA h g −1, principally by redox reactions on the nickel ions on distinct voltage plateaus at ∼3.6 V and ∼4.6 V.